2020
DOI: 10.3390/su12124859
|View full text |Cite
|
Sign up to set email alerts
|

Soil Health and Sustainable Agriculture

Abstract: A healthy soil acts as a dynamic living system that delivers multiple ecosystem services, such as sustaining water quality and plant productivity, controlling soil nutrient recycling decomposition, and removing greenhouse gases from the atmosphere. Soil health is closely associated with sustainable agriculture, because soil microorganism diversity and activity are the main components of soil health. Agricultural sustainability is defined as the ability of a crop production system to continuously produce food w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
156
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 340 publications
(164 citation statements)
references
References 179 publications
1
156
0
7
Order By: Relevance
“…Integrated nutrient management (INM) aims for optimal soil fertility and plant nutrition, increasing fertilizer input efficiency, decreasing environmental risks, and improving crop productivity through root/rhizosphere management [9]. Various models have been presented for sustainable soil management to increase the yield and produce nutritious and healthy products [22,23]. Regarding management methods, the application of organic and inorganic sources of nutrient elements has been used to obtain optimum productivity [9].…”
Section: Of 13mentioning
confidence: 99%
“…Integrated nutrient management (INM) aims for optimal soil fertility and plant nutrition, increasing fertilizer input efficiency, decreasing environmental risks, and improving crop productivity through root/rhizosphere management [9]. Various models have been presented for sustainable soil management to increase the yield and produce nutritious and healthy products [22,23]. Regarding management methods, the application of organic and inorganic sources of nutrient elements has been used to obtain optimum productivity [9].…”
Section: Of 13mentioning
confidence: 99%
“…A higher growth rate can be attributed to higher nutrient levels in greywater water compared to control (Table 1). Nutrient levels play a key role in plant morpho-physiology such as photosynthesis, root and shoot growth, and flower and fruit quality [27][28][29][30][31]. The significant increase in shoot growth is coupled normally with a reduction in nutrient and protein concentration in the tissues due to the dilution effect [32].…”
Section: Greywater Quality and Plant Yieldmentioning
confidence: 99%
“…It has been reported that NF can contribute to a holistic production management system that promotes and enhances agroecosystem health, including biodiversity, biological cycles, and soil biological activity [1][2][3]. Maintaining soil health, which includes the physical, chemical, and biological components, is a very crucial aspect in humanity's quest for sustainable agriculture, particularly crop production [4].…”
Section: Introductionmentioning
confidence: 99%